Rencana Pembangunan Lima Tahun Keempat sub sektor perkebunan, 1984/1985-1988/1989 (Departemen Pertanian, Direktorat Jenderal Perkebunan, 1984)
The Fourth Five Year Development Plan of the Directorate of Estate Crops for the plantation sector in Indonesia.